The Supply Chain Process Management Methodology within the Strategic Space and Considering the Leasing For Market Development - Pavel Ryabchuk; Igor Baev; Olga Zubkova; Dmitriy Korneev (International Journal of Supply Chain Management, 2020)
Abstract— The development of supply chain relations implies a methodological basis for assessing the supply chain process effectiveness that is adequate to the market development. The study contains a description of the methodology for assessing and managing the supply chain process from the perspective of the interests of the lessee and the external and internal environment factors. The study is based on the methodology for modeling cash flows of the recipient enterprise and the method of discounting its cash flows generated with the participation of the industrial enterprise in the supply chain process. The proposed methodology is a universal tool for assessing and managing the supply chain process, which includes the strengths of advanced methods for assessing the effectiveness of the supply chain scheme for financing industrial investments accumulated in scientific works devoted to supply chain. The proposed structure of strategic features based on the totality of the methods for assessing the supply chain activity, market development, and leasing process allows an industrial enterprise to generate the supply chain process management strategies based on the analysis of the performance indicators. A number of definitions have been introduced into the scientific discourse and a methodology for assessing the supply chain activity, market development, and leasing process has been developed. The assessment and management methodology is of practical value for a wide range of organizations considering the possibility of technological re-equipment of industrial production in a business network.